2014
DOI: 10.1371/journal.pone.0082507
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Brain Injury Induces Acute Post-Traumatic Sleep

Abstract: ObjectiveClinical observations report excessive sleepiness immediately following traumatic brain injury (TBI); however, there is a lack of experimental evidence to support or refute the benefit of sleep following a brain injury. The aim of this study is to investigate acute post-traumatic sleep.MethodsSham, mild or moderate diffuse TBI was induced by midline fluid percussion injury (mFPI) in male C57BL/6J mice at 9:00 or 21:00 to evaluate injury-induced sleep behavior at sleep and wake onset, respectively. Sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(106 citation statements)
references
References 48 publications
(77 reference statements)
8
97
0
1
Order By: Relevance
“…We observed a specific decrease in the number of long wakefulness bouts after mTBI, indicative of a decreased capacity to maintain wakefulness, which is also consistent with previous rodent literature (Lim et al, 2013;Rowe et al, 2013Rowe et al, , 2014Willie et al, 2012). This difference was only found in the first recorded 24 h, which is reminiscent of a study showing that sleep measured via piezoelectric cages predominates in the first hours after TBI .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed a specific decrease in the number of long wakefulness bouts after mTBI, indicative of a decreased capacity to maintain wakefulness, which is also consistent with previous rodent literature (Lim et al, 2013;Rowe et al, 2013Rowe et al, , 2014Willie et al, 2012). This difference was only found in the first recorded 24 h, which is reminiscent of a study showing that sleep measured via piezoelectric cages predominates in the first hours after TBI .…”
Section: Discussionsupporting
confidence: 91%
“…In parallel, secondary injury processes are immediately activated following brain injury. Glial cells release inflammatory mediators, such as interleukin-1 (IL-1) and tumor necrosis factor alpha (TNFa) Helmy et al, 2011;Rowe et al, 2013). These cytokines have specifically been shown to promote sleep and to alter the sleep EEG .…”
Section: Introductionmentioning
confidence: 99%
“…Cell morphology of cortical microglia in the control, sham operated rats, characterized by small spheric cell bodies with several primary, ramified processes, upon LFPI was changed and the signs of the microglia activation, such as swollen cell bodies with fewer, thicker, highly branched processes, appeared. The mentioned result is in accordance with previously described microglia activation obtained in other TBI models (Rowe et al, 2014;Susarla et al, 2014). Moreover, our results demonstrated that single administration of pioglitazone reduced the number of Iba1 positive cells in the cortex of the injured rats close to their number in rats of the control group.…”
Section: Parameters Of Inflammationsupporting
confidence: 93%
“…The righting reflex time is the total time from the initial impact until the rat spontaneously rights itself from a supine position. A righting reflex time of 5-10 min for all age groups was indicative of moderate injury and used as inclusion criteria for the study, as previously published [19,23,24,25,26]. In juvenile rats (PND 17), the presence of a seizure shortened the righting reflex times as juveniles consistently righted themselves immediately following injury-induced seizure.…”
Section: Methodsmentioning
confidence: 99%